PERANAN YAYASAN SWASTA TERHADAP PEMBERDAYAAN PETANI DESA DI DESA NGLANGGERAN, KECAMATAN PATUK, KABUPATEN GUNUNGKIDUL, DAERAH ISTIMEWA YOGYAKARTA - Foe, Jose Amadeus Krisna; Sunaryanto, Lasmono Tri (Hasanuddin University, 2020)
AbstractThe empowerment of village farmers by the private sector and the government has a significant difference. Three factors influence the impact of empowerment on improving the welfare of farmers, namely the quality of empowerment facilities, the intensity of empowerment facility provision, and the quality of empowerment facilitators. Nglanggeran Village farmers receive empowerment facilities from the regional government in the form of plant seeds, fertilizer, livestock germs, pens, and training once a year. This is only enough for one growing season and is often late. When empowered by the Obor Tani Foundation, farmers receive facilities in a package called the Farmers Empowerment Center. The facilities are in the form of ponds, farmhouses, agricultural production facilities, training on 11 pillars of agricultural cultivation, and farmer cadres to guide farmers for 3.5 years. When empowered by the government, farmers only produce for individual food needs and do not fix the main agricultural problems in the village. When empowered by the Obor Tani Foundation, farmers' incomes have risen as well as the main agricultural problem in the village which is lack of water can be solved. Farmer empowerment strategies undertaken by the Obor Tani Foundation can be used as learning by the government to improve the quality of farmer empowerment.Keywords: Farmer empowerment, Regional government, Non-government foundation.